PENGARUH ENVIRONMENTAL SOCIAL GOVERNANCE, KUALITAS AUDIT, DAN MANAJEMEN LABA TERHADAP PENGHINDARAN PAJAK - Rahmad Cahayadi; Lindawati Lindawati (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This study aims to determine the effect of environmental social governance, audit quality and earnings management on tax avoidance. This study uses tax avoidance as the dependent variable and environmental social, audit quality, and earnings management as independent variables. The population of this study is non-cyclical consumer sector companies listed on the Indonesia Stock Exchange in 2019 - 2023. By using purposive sampling technique, 9 companies were obtained that met the criteria for selecting data samples and have been analyzed with multiple linear regression analysis tests using the Eviews version 12 program. The results of the study on non-cyclical consumer sector companies obtained simultaneous results (f-test) showing that environmental social governance, audit quality, and earnings management variables have an effect on tax avoidance. While the partial results (t-test) of the environmental social governance variable have no effect on tax avoidance, and the audit quality variable has a negative effect on tax avoidance, and earnings management has no effect on tax avoidance. Keywords: Environmental Social Governance, Audit Quality, Earnings Management, And Tax Avoidance